Strategi Keunggulan Kompetitif Terhadap Kinerja Industri Kreatif Bordir Tasikmalaya - Lina Marlina; Agus Rahayu; Lili Adi Wibowo (IKOPIN, 2020)
Creative industries through Small and Medium Enterprises (SMEs) Embroidery is the industry with the most business units in Tasikmalaya City. The majority of these make management have to do a competitive advantage to gain market share. Competitive advantage strategies can be done with differentiation and cost leadership or low cost. Differentiation strategies emphasize innovation and cost leadership emphasizes proactive management. The competitive advantage strategy is back on the performance of SME management. Research uses quantitative through verifiative descriptive methods. Research object on the population of embroidery business units registered in the Ministry of Peridustrian and Perdaganan (Disperindag) Tasikmalaya City. Sample techniques use rondom sampling through questionnaires. Analysis techniques use multiple linear regressions with the help of SPSS 20. The results showed that the competitive advantage of differentiation had a significant positive effect on the creative industry performance of Tasikmalaya Embroidery SMEs. Cost leadership's competitive advantage strategy also has a positive effect on the creative industry performance of Tasikmalaya Embroidery SMEs.